Possible actions of methionine on embryonic development and postnatal phenotype of calves produced after embryo transfer - Masroor Sagheer; Quinn A. Hoorn; Oscar A. Ojeda-Rojas; Jeremy Block; Abigail J. Sproull; Daniella Heredia; Camila J. Cuellar; Tatiane S. Maia; McKenzie LJ. Haimon; Mariângela Bueno Cordeiro Maldonado; João H. Bittar; Angela M. Gonella-Diaza; et al. (Theriogenology, 2026)

First satellite track of a juvenile shortfin mako shark (Isurus oxyrinchus) in the Mediterranean Sea - Brendan D. Shea; Taylor K. Chapple; Khaled Echwikhi; Chiara Gambardella; Jeremy F. Jenrette; Stefano Moro; Robert J. Schallert; Barbara A. Block; Francesco Ferretti (Frontiers in Marine Science, 2024)

On the tracks of white sharks in the Mediterranean Sea - Francesco Ferretti; Brendan D. Shea; Chiara Gambardella; Jeremy F. Jenrette; Stefano Moro; Khaled Echwikhi; Robert J. Schallert; Austin J. Gallagher; Barbara A. Block; Taylor K. Chapple (Frontiers in Marine Science, 2024)
White sharks ( Carcharodon carcharias ) are among the most widespread, charismatic, and studied predators in the ocean. However, their conservation status is concerning in many ocean sectors, most notably the Mediterranean Sea, which hosts one of the least known and most endangered populations globally. Though they were historically abundant and widely distributed in the region, Mediterranean white sharks have declined to dangerously low abundance levels, impacted by centuries of coastal and, more recently, industrial fishing. The IUCN lists this species as Critically Endangered in the region, but information about its current abundance and ecology is scarce, hindering effective management and conservation. Here, we describe our initial effort to find and track the remaining Mediterranean white sharks and report what we have learned from these activities. In 2021-2023, we conducted three pilot expeditions in the Sicilian Channel, covering four major sites, collecting 159 eDNA samples, and carrying out 359 hrs of pelagic mid-water baited video surveys, 43 hours of deep-water benthic baited video surveys, and 111 hrs of fishing. Baited video surveys detected 42 species of bony fishes, elasmobranchs, marine mammals, and turtles. We detected white sharks at four sites from eDNA samples. Though we did not observe white sharks directly, these activities supported the identification of one of the last strongholds of this population in the region and started a multi-institutional white shark conservation program in the Mediterranean Sea, aiming to track the last white sharks in the region, estimate their abundance and extinction risk, characterize the species’ ecology and inform management and conservation.

Goat browse selectivity during conservation grazing in an invaded eastern oak-hickory forest - Wanderson Novais; Benjamin A. Wenner; Jeremy A. Block; Simon C. Power; Elizabeth Porteus; G. Matt Davies (Agroforestry Systems, 2023)

Detecting Mediterranean White Sharks with Environmental DNA - Jeremy Jenrette; Jennifer Jenrette; Kobun Truelove; Stefano Moro; Nick Dunn; Taylor Chapple; Austin Gallagher; Chiara Gambardella; Robert Schallert; Brendan Shea; David Curnick; Barbara Block; et al. (Oceanography, 2023)
The white shark (Carcharodon carcharias) is a globally distributed, ecologically important top predator whose biology and population dynamics are challenging to study. Basic biological parameters remain virtually unknown in the Mediterranean Sea due to its historically low population density, dwindling population size, and lack of substantial sightings. White sharks are considered Critically Endangered in the Mediterranean Sea, and recent analyses suggest that the population has declined by 52% to 96% from historical levels in different Mediterranean sectors (Moro et al., 2020). Thus, white shark sightings dating back to 1860 are being used to estimate population trajectories throughout the entire region. Though the population size is unknown, remaining individuals are thought to be primarily restricted to a handful of hotspots deemed important for their reproduction and foraging. One of these hypothesized hotspots is the Sicilian Channel, which accounts for 19% of total historical sightings.